PERILAKU AUDITOR ATAS PENERAPAN SISTEM REVIEW BERTINGKAT DALAM MANAJEMEN KAP (DALAM PERSPEKTIF TEORI KELAS) - Akie Rusaktiva Rustam (Jurnal Akuntansi Multiparadigma, 2010)
This research is a case study of Public Accounting Firm management behavior assessment in operational practices and management behavior analysis especially for audit practices implementation of hierarchical review system. The failure of the auditor in implementing audit process is called reduced audit quality (RAQ).  The research object is one of the local Public Accounting Firm in Malang which has not applied fair and appropriate organization structure and reward system yet.   Public Accountant Firm is a full professional organization, but in fact, based on Public Accountant  Firm practice and existence, especially in Malang, the organization structure, system and procedure as professionalism guarantee is informal organized, thus in developing and practicing, the element of management is organized based on board interest. Along with Hierarchical Review System implementation, auditor staff as an audit field worker would think this implementation as some form of suppression for them, mentally and financially. On Marx’s Class Theory perspective, hierarchical review system implementation showed different level of classes, higher and lower level. This different level of classes showed many problems and conflict of interest caused by unfair payment and job distribution. This problem can also cause Reduced Audit Quality (RAQ).